2011
DOI: 10.1111/j.1399-0039.2011.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil alloantigen genotype frequencies among blood donors with Turkish and German descent

Abstract: Antibodies against the human neutrophil antigens (HNA) are able to stimulate transfusion reactions, autoimmune and neonatal neutropenia. The aim of this study was to determine the HNA allele frequencies in the largest ethnic minority group in Germany in comparison with the German population for predicting the risk of alloimmunization and associated transfusion reactions, as well as the risk of developing neonatal neutropenia for the newborn of racial mixed couples. However, there exists no data about HNA genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 19 publications
4
43
1
1
Order By: Relevance
“…To date, all the results have been concordant with pre-typed controls. From the 1,520 platelet donor samples of the Basel and Zurich areas, HPA allele frequencies were well comparable to data previously reported for the Austrian population [62] while HNA allele frequencies are proving to be similar to those observed in Germany [63].…”
Section: Maldi-tof Ms In Transfusion Medicinesupporting
confidence: 73%
“…To date, all the results have been concordant with pre-typed controls. From the 1,520 platelet donor samples of the Basel and Zurich areas, HPA allele frequencies were well comparable to data previously reported for the Austrian population [62] while HNA allele frequencies are proving to be similar to those observed in Germany [63].…”
Section: Maldi-tof Ms In Transfusion Medicinesupporting
confidence: 73%
“…The frequency of the SNP indicative of the SLC44A2*1 and SLC44A2*2 alleles is known for Caucasian, African American, Han Chinese, Japanese, Tunisian, Brazilian, Thai, and other populations . Chu and colleagues applied an algorithmic approach to predict HNA antigens from whole genome sequencing (WGS) data.…”
mentioning
confidence: 99%
“…The FCGR3B*1 and FCGR3B*2 allele frequencies of the northern Thais did not differ from those of the Taiwanese and Japanese populations [9, 14]. Interestingly, the FCGR3B*1 and FCGR3B*2 allele frequencies were significantly different from those observed in the central Thai, German, Turkish, Tunisian, and Korean populations ( P <0.01) [16, 20, 21]. …”
Section: Resultsmentioning
confidence: 67%
“…Moreover, the FCGR3B locus was in Hardy-Weinberg equilibrium in Thai populations. The genotype frequency distribution of the central Thai population was also compared with that of the northern Thai population and other studies previously reported [9, 14, 16, 20, 21]. The FCGR3B*1 and FCGR3B*2 allele frequencies of the northern Thais did not differ from those of the Taiwanese and Japanese populations [9, 14].…”
Section: Resultsmentioning
confidence: 75%